KIF20A is associated with clinical prognosis and synergistic effect of gemcitabine combined with ferroptosis inducer in lung adenocarcinoma - He, Hua; Liang, Lu; Huang, Jingjing; Jiang, Shiyao; Liu, Yueying; Sun, Xiaoyan; Li, Yi; Cong, Li; Jiang, Yiqun (Frontiers in Pharmacology, 2022)
Gemcitabine (GEM), an antimetabolite that terminates DNA synthesis, is commonly used in the treatment of cancers including lung adenocarcinoma (LUAD). However, downregulation of sensitivity limits the therapeutic effect. Ferroptosis as the new form of regulated cell death has been shown to have great potential for cancer treatment with chemoresistance. Here, three genes with both ferroptosis and GEM-response-associated features were screened from RNA sequencing and public data for constructing an independent risk model. LUAD patients with different risk scores had differences in mutational landscape, gene enrichment pathways, and drug sensitivity. By Cell Counting Kit-8 assay, flow cytometry, and colony forming assay, we demonstrate that GEM and ferroptosis inducer (FIN) Imidazole Ketone Erastin had a synergistic combined anti-proliferative effect on LUAD cells and knockdown of KIF20A (the core gene of our model) further enhanced cell death in vitro by inducing ferroptosis. In conclusion, we identified a link between ferroptosis and GEM response in LUAD cells and developed a robust signature that can effectively classify LUAD patients into subgroups with different overall survival. For LUAD, the combined treatment modality of GEM and FIN is potentially effective and KIF20A may be a new therapeutic target.